Death after trauma in the rural High North - Bakke, Håkon Kvåle (University of Tromsø, 2013)
Papers 3 of this thesis are not available in Munin: 3. Håkon Kvåle Bakke, Trond Dehli and Torben Wisborg: 'Fatal injury caused by low-energy trauma – a 10-year rural cohort' (manuscript) The work of this thesis was initiated because Finnmark County had a mortality rate from external causes well above national average for several decades. The aims of the thesis were to 1) investigate possible reasons for Finnmark’s’ elevated death rate from external causes, 2) identify challenges that a trauma system in Scandinavia must be tailored to meet, and 3) find access points to limit the burden of injury in Finnmark. The thesis consists of four papers. The first paper gives an epidemiological description of the deaths from trauma in Finnmark for a ten-year period, and explores changes over time. In the second article the epidemiology of trauma death in Finnmark is compared to Hordaland County. The third paper describes the deaths from low energy trauma in Finnmark County for the ten-year period. The fourth paper is a review of the literature on first aid to trauma victims by bystanders. We have found an urban-rural continuum where mortality, and share of prehospital death increases with rurality. For RTAs the rate of accidents with personal injury was distributed inversely to mortality along the continuum. The most common modes of injury were fractures in elderly, suicide, and road traffic accidents. There is a potential for injury mortality reduction in first aid from laypeople, but literature in that field is very sparse. Low energy trauma constitutes a considerable and underestimated share of deaths from trauma, and the victims are older and with higher pre-injury morbidity than victims of high energy trauma. The overall mortality from external causes in Finnmark has declined from the early 90’s to the mid-2000, but the epidemiological pattern of injury is otherwise unchanged. Finnmark’s high rate of death from external causes is probably tied to the county’s rural nature and the multi-faceted disadvantage of ...